2021
DOI: 10.48101/ujms.v126.8124
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the relationship between systemic immune-inflammation index and mortality in patients with hypertrophic cardiomyopathy

Abstract: Background: This study investigates the predictive value of the systemic immune-inflammation index (SII), which was calculated as platelet × neutrophil/lymphocyte ratio, for all-cause mortality in patients with hypertrophic cardiomyopathy (HCM). Methods: A total of 360 HCM patients were enrolled. They were divided into three groups based on the tertiles of baseline SII. The association between SII and all-cause mortality was analyzed. Results: There were 53 HCM patients who died during a mean follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…41 Wang Z found that SII index was a significant risk factor for all-cause mortality in HCM patients. 42 Agus HZ also revealed that high SII levels are independently associated with in-hospital mortality and patients with infective endocarditis were predicted well by the SII index. 43 The high SII index levels can predict an increased risk of 30-day and 90-day in-hospital mortality, as well as major adverse cardiac events in critically ill CHF patients.…”
mentioning
confidence: 94%
“…41 Wang Z found that SII index was a significant risk factor for all-cause mortality in HCM patients. 42 Agus HZ also revealed that high SII levels are independently associated with in-hospital mortality and patients with infective endocarditis were predicted well by the SII index. 43 The high SII index levels can predict an increased risk of 30-day and 90-day in-hospital mortality, as well as major adverse cardiac events in critically ill CHF patients.…”
mentioning
confidence: 94%
“…[19–23] Several studies demonstrated that higher SII was an important prognostic and predictive marker in various cardiovascular diseases such as: severity of CAD in patients with stable angina pectoris [7] aortic stenosis patients who underwent transcatheter aortic valve implantation [24] and hypertrophic cardiomyopathy. [18] All these results demonstrate the importance of SII in inflammation which has an essential role in the development of cardiovascular events.…”
Section: Discussionmentioning
confidence: 81%
“…Furthermore, since a LV thrombus can already be identified during hospitalization period following acute MI, identification of early predictors of LV thrombus is required. [16] Recently, Hu et al [17,18] have advanced an easily accessible inflammation-based marker called the SII that brings together 3 inflammatory peripheral cell counts to consider patients' immune and inflammatory status together based on routine blood tests. It has been widely studied in different cancers and SII was shown to be a strong predictor of worse clinical outcomes in cancer patients and several other disease states.…”
Section: Discussionmentioning
confidence: 99%
“…Resident memory T cells are an integral component of the immune sensing network, participating in protecting individuals from various pathogenic mechanisms 36 . During the development of HCM, changes in myocardial tissue are specified in three phases, including the activation of fibrotic pathways and platelet in the intermediate phase, which may be associated with the phenotypic variability of HCM 37 . The human heart contains a resident macrophage population that expands in response to damage.…”
Section: Discussionmentioning
confidence: 99%